The effect of learning strategies adopted in K12 schools on student learning in massive open online courses. - Tang, Shan; Lei, Chi‐Un; Wei, Hong Qiang (Journal of Computer Assisted Learning, 2024)
Background: Given students' lack of self‐directed learning skills and the growing concern about implementing massive online open courses (MOOCs) in K12 education, learning strategies are needed to facilitate MOOC learning. Many studies have provided different strategies for effective learning in MOOCs. However, there is still limited research to confirm whether these strategies effectively support MOOC learning when deployed by secondary schools, which are not MOOC developers. Objectives: This mixed‐method study examines the provision of different learning strategies, including a learning guide, an academic mentoring programme, a training workshop, and a reimbursement scheme, and investigates the impact of these strategies on student learning in MOOCs. Methods: The study uses two data sources: (1) surveys with 40 participants and (2) semi‐structured interviews with 12 participants. The quantitative data were analysed with descriptive statistics and Fisher's exact test, and the qualitative data were analysed with thematic analysis. Results and Conclusion: The findings indicate that MOOC learners had positive attitudes towards the overall school support, with mentoring enjoying great popularity amongst the students. In terms of the effectiveness of the school support, the mentoring programme and reimbursement scheme were more effective than the university training and learning guide. The paper discusses the implications for researchers and educators. Lay Description: What is already known about this topic: There are a large number of K12 MOOC implementations, which are (i) STEM‐related and computer science courses, and (ii) from Europe and the USA.Limited studies provided different learning strategies for MOOC learning from the perspective of K12 schools, which are not MOOC developers.There is a need to explore MOOC initiatives encompassing a wide variety of subjects, including computer science MOOCs and non‐computer science MOOCs, in regions beyond Europe and the USA.There is also a need for further scrutiny of the effectiveness of learning strategies provided by the K12 school. What this paper adds: Our study launched the first MOOC implementation in K12, encompassing several subject areas beyond computer science in the region of Asia.Our study provided different learning strategies adopted by the K12 school, and the analysis revealed that MOOC learners took positive attitudes towards overall school support with mentoring enjoying great popularity with these students.Our study examined the effectiveness of school support and identified that mentoring and reimbursement are more effective than university training and the learning guide. Implications for practitioners: The insights gained from the study enable other K12 schools and educators to implement MOOC into existing school infrastructures successfully.These strategies provided in the MOOC implementation program can be helpful in many different online learning contexts.